Evaluating self-declared ancestry of U.S. Americans using autosomal, Y-chromosomal and mitochondrial DNA - (:unkn) unknown (My University, 2010)
The current U.S. population represents an amalgam of individuals originating mainly from four continental bio-geographic ancestries (Africa, Europe, Asia and America). We have analyzed paternally, maternally and bi-parentally inherited DNA markers sensitive for indicating continental genetic ancestry in all four major U.S. American groups. We found that self-declared U.S. Hispanics and U.S. African Americans tend to show variable degrees of continental genetic admixture among the three genetic systems, with evidence for a marked sex-biased admixture history. Moreover, we observed significant regional variation across the country in genetic admixture. In contrast, self-declared U.S. European and U.S. Asian Americans were genetically more homogeneous at the continental ancestry level. Two autosomal ancestry-sensitive markers located in skin pigmentation candidate genes showed significant differences in self-declared U.S. African Americans or U.S. European Americans, relative to their assumed parental populations from Africa or Europe. This provides genetic support for the importance of skin color in the complex process of ancestry identification.
Keywords: African Research